(96) Economic Models: Definitions & Classification النماذج الاقتصادية : التعريفات والتصنيف - M. M. El-Imam (معهد التخطيط القومى, 2023)
This study represents a comprehensive crystal clear definition of economic models plus how the way to build them. It shows , also , the rules of their classification and specification.